CHARACTER’S OBSESSION FOR PERFECTION IN THE AVIATOR MOVIE BY MARTIN SCORSESE: A PSYCHOANALYSIS - Misnawati Misnawati; Budi Eko Pranoto (English Literature Study Program, Faculty of Arts and Education Universitas Teknokrat Indo, 2022)
Obsession for perfection is common behavior that may be suffered by people. Those who are so obsessed with something are easily sacrifice anything to chase the perfection that has already been created in their minds. It is possible that they will perhap harm themselves. Therefore, this research aimed to analyze the obsession for perfection in The Aviator movie 2012 by Martin Scorsese by using Psychoanalytic theory. This research applied an in-depth qualitative narrative analysis method which examines the story elements from dialogue and picture collected in the form of screen-capture of the relevant scene. This research used psychoanalytic theory as the approach and divided the analysis into two sub discussions; they are the reflection of obsession for perfection and the effects of obsession for perfection. Based on the analysis, the data supports the findings that Howard suffers some conditions which includes Target Oriented; where people with ambitions like this have all-or-nothing thinking. The second finding is Highly Dependent on Result; it shows that Howard put his self-esteem depends on what is accomplished and how others respond to what he would achieve. Keywords: The Aviator movie, Obsession, Obsession for Perfection, Psychoanalytic theory Amelia, D. Daud, J. (2020). Freudian Tripartile on Detective Fiction: The Tokyo Zodiac Murders. Language Literacy: Journal of Linguistics, Literature and Language Teaching, 4(2), 299-305.Bogdan, R. C., Biklen, S. K. (1992). Qualitative Research for Education. Boston: Allyn and Bacon.Butler, J. (1999). Gender Trouble Feminism and Subversion of Identity. New York and London: Routledge.Cabrera, S. F., Sauer, S. J., Thomas-Hunt, M. C. (2009). The evolving manager stereotype: The effects of industry gender typing on performance expectations for leaders and their teams. Psychology of Women Quarterly, 33(4), 419–428.Cai, Mingshui (1992). Multicultural Literature for Children and Young Adults. Multicultural Literature for Children and Young Adults, Reflections on Critical Issues, Greenwood Press. Pdf.Casad, B.J. Wexler, B.R. (2017). Gender Roles. In The SAGE Encyclopedia of Psychology and Gender. (Ed.) Kevin L. Nadal.Casad, BJ and Bryant, WJ (2016) Addressing Stereotype Threat is Critical to Diversity and Inclusion in Organizational Psychology. Frontiers in Psychology, 7(8), 1-18. doi: 10.3389/fpsyg.2016.00008Creswell, J. W. (2007). Qualitative Inquiry and Research Design: Choosing Among Five Approaches (Second). Thousand Oaks, CA: Sage Publication.Dahl, Roald (1954). Lamb to the Slaughter. https://www.rsf.gsacrd.ab.ca/eteacher_download/1119/35642Denzin, N. K., Lincoln, Y. S. (Eds.). (2005). The Sage Handbook of Qualitative Research (Third Edit). California: Sage Publications, Inc.Eagly, A. H., Karau, S. J., Makhijani, M. G. (1995). Gender and the effectiveness of leaders: A meta-analysis. Psychological Bulletin, 117, 125-145. doi:10.1037/0033- 2909.117.1.125Fithratullah, M. (2021). Representation of Korean Values Sustainability in American Remake Movie. Teknosastik: Jurnal Bahasa dan Sastra, 19(1), 60-73.Gulö, I., Rahmawelly. (2018). An Analysis of Omission in Students’ English Writings. Teknosastik: Jurnal Bahasa dan Sastra, 16(2), 55-59.Kasih, E. N. E. W., Amelia, D., and Fithtratullah. M. (2021). Unraveling Students’ Attitude of Using Blog for Online Learning in Literature Class. Universitas Riau International Conference on Education Technology (URICET), pp. 419-424, doi: 10.1109/URICET53378.2021.9865946.Kasih, E. N. (2018). Redefining Hybridity of Chicano Literature in Jimenez’s Fictions. International Journal of Diaspora Cultural Criticism, 8(2), 294-319.Kasih, E.N., Strid, J.E. (2020). Reconstructing the Border: Social Integration in Reyna Grande’s The Distance Between Us. International Journal of Innovation, Creativity and Change, 14(9), 702-715.Khandelwal, P. (2002). Gender stereotypes at work: implications for organizations. Indian Journal of Training and Development, 32(2), 72–83.Kuswoyo, H. (2016). Thematic Structure in Barack Obama’s Press Conference: A Systemic Functional Grammar Study. Advances in Language and Literary Studies, 7(2), 257-267. https://doi.org/10.7575/aiac.alls.v.7n.2Miller, L. M. and Lachman, M. E. (2000) Cognitive Performance and the Role of Control Beliefs in Midlife. Aging, Neuropsychology, and Cognition, 7(2), 69-85.Milyavsky M, Kruglanski AW, Chernikova M, Schori-Eyal N. (2017). Evidence for arrogance: On the relative importance of expertise, outcome, and manner. PLoS ONE, 12(7), 1-31. https:// doi.org/10.1371/journal.pone.0180420Rido, A. and Sari, M.S. (2018). Characteristics of Classroom Interaction of English Language Teachers in Indonesia and Malay. International Journal of Language Education, 2(1), 40-50.Sriastuti, A., Adi, R.A., Rokhman, M.A. (2021). Capitalism and Socialism As Ideological Constructions In American Dystopian Novels. Rubicon, 8(2), 91-105Tabassum, N. and Nayak, S. (2021). Gender Stereotypes and Their Impact on Women’s Career Progressions from a Managerial Perspective. IIM Kozhikode Society Management Review 10(2) 192–208.